The Neural Mechanism Underlying Cognitive and Emotional Processes in Creativity - Gu, Simeng; Gao, Mengdan; Yan, Yaoyao; Wang, Fushun; Tang, Yi-yuan; Huang, Jason H. (Frontiers in Psychology, 2018)
Creativity is related to both cognition and emotion, which are the two major mental processes, interacting with each other to form psychological processes. Emotion is the major drive force of almost all creativities, sometimes in an unconscious way. Even though there are many studies concerning the relationship between creativity and cognition, there are few studies about the neural mechanisms of the emotional effects on creativity. Here we introduce a novel model to explain the relationship between emotions and creativities: Three Primary Color model, which proposes that there are four major basic emotions, which are subsided by three monoamines, just like the three primary color: dopamine-joy, norepinephrine-stress (fear and anger), and serotonin-punishment. Interestingly, these three neuromodulators play similar roles in creativity, whose core features are value and novelty (surprise), like the features of the core features of basic emotions (hedonic value and arousal). Dysfunctions of these neuromodulators might be the reasons for both psychopathology and creation, in that they can change the thinking styles such as novelty seeking behavior, hyper-connectivity of brain areas, and/or cognitive disinhibition to induce both creativity and psychopathology. This new model will not only help researchers understand the dynamic of basic emotion elements, it can also bring an entirely new perspective into the relationship between psychopathology and creativity.